The Contextual Meaning of 'Tyranny' in the poem Ila Tugati al-'Alam by Abu al-Qasim al-Syabi: A Semantic Analysis - Risadatul Ulwiyah (Islah: Journal of Islamic Literature and History, 2023)
This study aims to describe the contextual meaning in the poem Ila T}uga>ti Al-'Ala>m by Abu Al-Qa>sim Al-Sya>bi based on semantic analysis. The method used in this study is a qualitative descriptive analysis. As the source of data, the poem is a part of the diwan of shaykh Abu Al-Qa>sim Al-Sya>bi published in 2005 in Beirut and revived in 2011 during the Egyptian revolution. The poem is analysed based on lexical and contextual meanings to obtain the in-depth message within the poem. The results show that the sentences found within have different meanings from their lexical meanings. This is based on the context of the poem. In this context, the poet attempts to portray the significance of the Egyptian rulers or leaders at the time who were authoritarian and nicknamed as the 'tyrants of the world'. The stanzas become the moaning of the people who are suffering from tyrannical and arbitrary leadership. Besides, this poem includes threats and rejection of policies that bring misery and suffering to the people.